2019
DOI: 10.1016/j.euf.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Primary Penile Cancer: The Role of Adjuvant Radiation Therapy in the Management of Extranodal Extension in Lymph Nodes

Abstract: Background: In head and neck cancer, the presence of extranodal extension (ENE) in lymph nodes (LNs) has been shown prospectively to require adding chemotherapy to postoperative radiation therapy (RT). Limited data exist regarding ENE in LNs from primary penile cancer (PeCa). Objective: To determine the association of RT and ENE in PeCa. Design, setting, and participants: We retrospectively analyzed the outcomes of 93 patients with pT1-4 N3 M0 (American Joint Committee on Cancer 7th edition) squamous cell carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
(22 reference statements)
0
16
0
Order By: Relevance
“…Radiotherapy with concurrent chemotherapy has become a standard management strategy for head and neck, vulvar, and anal squamous cancers, [56][57][58] but its use in the perioperative setting in penile cancer is limited by the small number of available studies. 59 The EAU penile cancer guideline group recently conducted a systematic review of the evidence and concluded that because of the heterogeneous and limited evidence of clinical benefit, a routine recommendation of adjuvant radiotherapy is not yet warranted. 60 In conclusion, the current standard of care is founded on limited data but remains as neoadjuvant chemotherapy with TIP as the preferred regimen, followed by surgical treatment.…”
Section: Role Of Adjuvant Radiation Therapymentioning
confidence: 99%
“…Radiotherapy with concurrent chemotherapy has become a standard management strategy for head and neck, vulvar, and anal squamous cancers, [56][57][58] but its use in the perioperative setting in penile cancer is limited by the small number of available studies. 59 The EAU penile cancer guideline group recently conducted a systematic review of the evidence and concluded that because of the heterogeneous and limited evidence of clinical benefit, a routine recommendation of adjuvant radiotherapy is not yet warranted. 60 In conclusion, the current standard of care is founded on limited data but remains as neoadjuvant chemotherapy with TIP as the preferred regimen, followed by surgical treatment.…”
Section: Role Of Adjuvant Radiation Therapymentioning
confidence: 99%
“…Secondly, adjuvant therapies are infrequently used as a rule in PeCa: only in about one of seven cases in our review. This is because the limited data reveals only a potential role for RT in selected primary lesions [2] and in pN3 patients [4] , [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the use of radiotherapy for nodal metastases is not recommended 33 . However, emerging research suggests that radiotherapy can improve regional control in PC patients with involved pelvic lymph nodes 34 without extranodal extension 35 .…”
Section: Advances In the Management Of Metastatic Diseasementioning
confidence: 99%